Building Digital Loyalty: The Power of Customer Experience and E-Service Quality - Almas, Idan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Amid the intense competition in Indonesia's digital service industry, understanding the factors that influence customer loyalty is crucial for companies to maintain their market presence. This study aims to analyze the influence of brand image, customer experience, and e-service quality on customer loyalty. This is a quantitative research using data collection and analysis tools designed to explain causal relationships between research variables through hypothesis testing. The sampling technique used was non-probability sampling, specifically purposive sampling. The sample consisted of 100 respondents who were at least 17 years old, users of the By.U digital internet service, residing in Malang City, and had subscribed to the service at least twice. The data was processed using SPSS 24. The hypothesis testing results show that (1) brand image has a positive but not significant effect on customer loyalty, (2) customer experience has a positive and significant effect on customer loyalty, and (3) e-service quality has a positive and significant effect on customer loyalty. These findings offer strategic insights for digital service providers to enhance service quality and customer experience in order to build long-term loyalty. The practical implication is that companies should prioritize strengthening customer experience and e-service quality as key strategies to retain their customer base.